2017
DOI: 10.2500/aap.2017.38.4069
|View full text |Cite
|
Sign up to set email alerts
|

Fluticasone propionate and fluticasone propionate/salmeterol multidose dry powder inhalers compared with placebo for persistent asthma

Abstract: Delivery of Fp and FS via the novel MDPI provided significant clinical benefits and was well tolerated in patients with persistent asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…These values differ from the reports of drug efficacy, which evaluated its outcomes in a short time (twelve weeks); these studies showed an increase in FEV 1 >15% with the use of ICS/LABA. 28 , 29 A similar change was identified in the AG from t0 to t1, and after this time, it did not change significantly. Specifically, in the context of N-ERD, most studies have evaluated the beneficial role of desensitization.…”
Section: Discussionsupporting
confidence: 68%
“…These values differ from the reports of drug efficacy, which evaluated its outcomes in a short time (twelve weeks); these studies showed an increase in FEV 1 >15% with the use of ICS/LABA. 28 , 29 A similar change was identified in the AG from t0 to t1, and after this time, it did not change significantly. Specifically, in the context of N-ERD, most studies have evaluated the beneficial role of desensitization.…”
Section: Discussionsupporting
confidence: 68%
“…The database searches yielded 1109 unique publications and six records were identified through other sources (Figure 1). Overall, 27 publications that described the results from 19 unique studies [37,38,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] were included in the SLR, of which 15 studies [37,38, 49,50,52-55, 57-62, 55-68] were deemed suitable for inclusion in the base case NMA (Table 2).…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…In the first trial, Sher et al 8 evaluated the efficacy and safety of fluticasone propionate and fluticasone propionate/salmeterol multidose dry powder inhalers compared with placebo for persistent asthma. In the second trial, Vanderwalker et al 9 evaluated the efficacy and safety of beclomethasone dipropionate breath-actuated or metered-dose inhaler in pediatric patients with asthma.…”
mentioning
confidence: 99%